Antibacterial and bioactive composite bone cements containing surface silver-doped glass particles. (20th October 2015) - Miola, Marta; Fucale, Giacomo; Maina, Giovanni; Verné, Enrica
Abstract: A bioactive silica-based glass powder (SBA2) was doped with silver (Ag + ) ions by means of an ion-exchange process. Scanning electron microscopy (SEM), energy dispersion spectrometry (EDS) and x-ray diffraction (XRD) evidenced that the glass powder was enriched with Ag + ions. However, a small amount of Ag2 CO3 precipitated with increased Ag concentrations in the exchange solution. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of Ag-SBA2 towards Staphylococcus aureus were also evaluated and were respectively 0.05 mg ml −1 and 0.2 mg ml −1 . Subsequently, Ag-SBA2 glass was used as filler (30%wt) in a commercial formulation of bone cement (Simplex ™ P) in order to impart both antibacterial and bioactive properties. The composite bone cement was investigated in terms of morphology (using SEM) and composition (using EDS); the glass powder was well dispersed and exposed on the cement surface. Bioactivity tests in simulated body fluid (SBF) evidenced the precipitation of hydroxyapatite on sample surfaces. Composite cement demonstrated antibacterial properties and a compressive strength comparable to the commercial formulation.